Feasibility Analysis of CareToy-Revised Early Intervention in Infants at High Risk for Cerebral Palsy - Beani, Elena; Menici, Valentina; Cecchi, Alessandra; Cioni, Maria Luce; Giampietri, Matteo; Rizzi, Riccardo; Sgandurra, Giuseppina; Cioni, Giovanni, CareToy-R Consortium; Artese, Claudia; Barzacchi, Veronica; Cervo, Marta; et al. (Frontiers in Neurology, 2020)
Infants with perinatal brain injury are at high risk for Cerebral Palsy (CP). Progresses in detection of early signs of brain injury and of CP allow Early intervention (EI) programs for improving the outcome of these infants. CareToy system (CT), developed within an European project (Trial Registration: NCT01990183) allows to provide, by means of tele-rehabilitation, a highly personalized, family-centred, home-based EI for young infants, remotely managed by clinicians. CareToy, already used with preterms without brain injury, has been adapted for high-risk infants in a project funded by the Italian Ministry of Health and the CareToy-Revised (CareToy-R) has been realized (Trial registration: NCT03211533 and NCT03234959). Before assessing its efficacy, it was crucial to evaluate acceptability, usability and feasibility of CareToy-R EI. 19 high-risk infants with perinatal brain injury, aged 5.95± 2.13 months (range 3.12-10.78 months), carried out a 8 weeks training with CareToy-R at home, performing customized playful activities with their parents, tailored on their rehabilitative needs, remotely managed by clinicians. The feasibility of training and study procedures were assessed through criteria derived from literature; acceptability and usability have been analyzed from data about individual training and an ad-hoc questionnaire. All CareToy-R trainings were planned by the clinical staff with a daily personalized use per each infant between 30 and 45 minutes (mean 34.37). The amount of executed training by the infants was very high (daily mean 30.30 minutes), with no differences related to infant age, sex and gestational age. All the 9 feasibility criteria were achieved, family compliance to the project was very good, data collection was completed and CareToy-R system worked properly and easily for parents. The answers of the questionnaire had a total mean score of 84.49% and they ranged from a minimum of 81.05% (in “easy to use” area) to a maximum of 86.49 (“changes due to the training” area),with no differences related to nationality or familiarity with technology of the mothers. This study reports preliminary evidence to the feasibility of an home-based EI with CareToy-R system in infants at high-risk for CP. Results of the RCT will provide data about the potential effectiveness of this approach.